Comparison of Prior Administration of Intravenous Dexmedetomidine and Lidocaine on Pain during Propofol Injection for Induction of General Anaesthesia in Patients Undergoing Elective Oral and Maxillofacial Surgery - Mazhar, Tehzeeb; Aatir Fayaz, Muhammad; Usman Mohsin, Muhammad; Kaleem Sattar, Muhammad; Adnan, Muhammad; Sultan, Atqua (Biological and Clinical Sciences Research Journal, 2025)
Pain upon propofol injection is a common adverse effect during induction of anaesthesia. Lidocaine and dexmedetomidine are frequently used to mitigate this discomfort, but their comparative efficacy remains unclear. Objective: To compare the effectiveness of intravenous lidocaine and dexmedetomidine in reducing pain intensity due to propofol injection in patients undergoing elective oral and maxillofacial surgery. Methodology: This prospective study was conducted in the Department of Anesthesia and ICU at Nishtar Medical University, Multan, from June 7 to December 7, 2023. A total of 190 patients were randomly assigned to two groups: Group A received dexmedetomidine, and Group B received lidocaine. Baseline parameters, including gender, age, BMI, obesity, ASA physical status, and residential area, were recorded. Pain intensity during propofol injection was assessed and compared between the groups using the chi-square test, with a p-value ≤ 0.05 considered statistically significant. Results: The mean BMI was 26.50 ± 1.68 kg/m² in Group A and 25.98 ± 2.10 kg/m² in Group B, with obesity present in 9.5% and 11.6% of patients, respectively. Diabetes was observed in 10.5% of Group A and 12.6% of Group B. ASA physical status type I was noted in 83.2% of Group A and 80% of Group B. Pain was absent in 56.8% of patients in Group A and 62.1% in Group B, showing no statistically significant difference (p > 0.05). Conclusion: Both lidocaine and dexmedetomidine are equally effective in reducing pain associated with propofol injection and can be used interchangeably without significant adverse effects.